Study of oral hygienic practices and oral health status among school children in Jabalpur, Madhya Pradesh: a cross-sectional study - Tomar, Shashi Prabha; Kasar, Pradeep Kumar; Tiwari, Rajesh (International Journal Of Community Medicine And Public Health, 2017)
Background: Oral hygiene should be educated and practiced at early age as it is one of the determinants of the health state later in one’s life. Considering the fact that there is the rise in the number of dental problems in school going children, the present study was undertaken to find out the oral hygienic practices among school going children and assess their oral health status. Methods:A cross sectional study carried out in 150 school children from two schools near medical area Jabalpur (75 from each school)between the age group of 10-15 years. A p-value of <0.05 was considered statistically significant for applied statistical tests. Results: The present study showed that only 34 % children had habit of brushing both time morning and at night before going to bed. Only 22% of children used correct brushing technique. Most common malpractice among children was eating chalk 12%. Regarding oral health status of school children dental caries 54.7% followed by dental cavities (52.7%) were most common problems found. Conclusions:Oral hygienic practices were poor needs educational motivation regarding duration of brushing, appropriate way to brush the teeth, and use of mouthwash.